2022
DOI: 10.1177/00914509221094893
|View full text |Cite
|
Sign up to set email alerts
|

Chemsex in Lisbon? Self-Reflexivity to Uncover the Scene and Discuss the Creation of Community-Led Harm Reduction Responses Targeting Chemsex Practitioners

Abstract: This essay is based in a self-reflexive collective process and intends to present the chemsex scene in Lisbon and harm reduction responses implemented to address the needs of chemsex practitioners. The analysis considered professional experiences, participant observation, literature review of the relevant data in Portugal and autoethnographic data from a chemsex practitioner and peer educator. This essay aims to present the community-led creation of a transdisciplinary collaborative network able to assess and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Another important benefit of the current study is that the intervention was found to reduce the participants’ intention to have chemsex and their actual engagement in chemsex. Given that chemsex tends to be hidden and private and that those who practice chemsex are difficult to reach [ 37 ], eHealth interventions can provide MSM with a private, anonymous, and easily accessible platform offering supportive care and useful information. The current study provides empirical evidence for governments, health authorities, and other stakeholders to put more resources into delivering chemsex-preventive interventions and care using online platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Another important benefit of the current study is that the intervention was found to reduce the participants’ intention to have chemsex and their actual engagement in chemsex. Given that chemsex tends to be hidden and private and that those who practice chemsex are difficult to reach [ 37 ], eHealth interventions can provide MSM with a private, anonymous, and easily accessible platform offering supportive care and useful information. The current study provides empirical evidence for governments, health authorities, and other stakeholders to put more resources into delivering chemsex-preventive interventions and care using online platforms.…”
Section: Discussionmentioning
confidence: 99%
“…The participants' reflections on the support resources are important for orienting the discussion on the intervention practices that should be put in place for people practising chemsex. Presently, the scientific literature on this question mostly focusses on recommendations directly related to the repercussions of chemsex [22,23] or more recently on the narratives of community organization practices [23,25,32]. We are proposing to analyze the results presented above by making connections with affirmative intervention practices, which seem to be a promising approach for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Given the highly defined context of this research, limited to people who use methamphetamine in the context of chemsex in Quebec, we must underline that fact that it is difficult to transfer these study results given the limited parameters of the sample. Additional research, that takes into account certain local cultural specificities related to chemsex, in particular with respect to the psychoactive substances used by the community, and associated practices [32], should be conducted in order to develop a better grasp of the transversal needs of people practising chemsex.…”
Section: Discussionmentioning
confidence: 99%
“…Úgy tűnik, hogy ez a szükséglet (autoagresszív önkifejezés) az adoleszcens évekre jellemző, a zenei és szubkulturális aláfestés pedig mindig változik. Kvalitatív kutatások szerint a szubkulturális önkárosítás összefüggésbe hozható a drogfogyasztással, a gender-diverzitással, a társadalmi nemhez kötött erőszakkal (gender-based violence), valamint a chemsexszel (Pires, Gomes, Caldas & Cunha, 2022). A chemsex a szintetikus kábítószerek és a szexuális élet együttes élvezetét és az azzal kapcsolatos életstílust jelenti.…”
Section: Vérunclassified